L’enseignement et l’évaluation de la compétence sociolinguistique: quels outils pour quels objectifs? - Falkert, Anika (Ponti/Ponts, 2021)
Communicative competence as defined in the CEFR encompasses linguistic, pragmatic and sociolinguistic competence. The latter “relates to the knowledge and skills required to make language work in its societal dimension” (Council of Europe 2001: p. 93). However, the discrepancy between teaching tools, reference texts such as the CEFR and assessment systems generates a number of tensions, and even inconsistencies, between the objectives pursued and the means used. This contribution aims to sketch out some ideas for a better connection between foreign language teaching and assessment of sociolinguistic competence in FLE. We will thus show that the evaluation of this competence entails the implementation of teaching practices largely based on metacognition.